Fulfillment Of Human Rights For The Poor And Abandoned Children - Muhammad Refri Bintang Pamungkas; Muhammad Kamal Hidjaz; Sri Amlinaty Muin (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to determine the Makassar City Government's efforts to fulfill the rights of the poor and neglected children in Makassar City, and also to analyze the factors in Makassar City Government legal policies that impact the fulfillment of rights for the poor and neglected children in Makassar City. The method used in this study is empirical legal research, namely legal research that uses empirical data through observations in real situations to explain a research. The results of this study indicate that efforts to fulfill the rights of street children, beggars, and vagrants are not yet optimal. This is due to several factors, including internal government initiatives, community participation, and customs. This research recommends that the government implement substantial programs that truly address the rights of the poor and neglected children, rather than simply being implemented on a whim or for a short period of time.